Insulated Solar Electric Cooking: Tomorrow's healthy affordable stoves? - T. Watkins; P. Arroyo; R. Perry; R. Wang; O. Arriaga; M. Fleming; Christopher O'Day; I. Stone; J. Sekerak; D. Mast; N. Hayes; P. Keller; et al. (Development Engineering, 2017)
We present a cooking technology consisting of a solar panel directly connected to an electric heater inside of a well-insulated chamber. Assuming continued decrease in solar panel prices, we anticipate that in a few decades Solar Electric Cooking (SEC) technologies will be the most common cooking technology for the poor. Appropriate use of insulation reduces the power demand making low-power Insulated Solar Electric Cooking (ISEC) systems already cost competitive. We present a 100 prototype and preliminary results of two implementations in Uganda.
Keywords: 330